Impacts of lining, maintenance and operations on water delivery performance in Pakistan - Murray-Rust, Hammond; Vander Velde, E.J.; Merrey, Douglas J. (1993)
A comparative study of hydraulic performance of three secondary canals in Pakistan's Punjab was undertaken to determine the relative benefits of three physical interventions: (1) focusing standard maintenance inputs using a computer-based model to analyze the effects of work in specific locations in a small distributary, (2) major desilting involving mechanical excavation of sediment in a medium sized canal, and (3) lining of the lower two-thirds of a major distributary. The results indicate that the greatest improvement in hydraulic performance was obtained from the least expensive intervention, focused maintenance: for a capital cost of $0.52 per ha, the inequity ratio between the head quarter and tail quarter of the canal declined from 4.2 to 1.3. For mechanical desilting the investment was $2.54 per ha, resulting in a reduction in inequity from 6.1 to 2.6. The benefits from this intervention would need to last at least 15 years to be economically competitive with focused maintenance inputs. Lining proved to be unjustified in the study location: although the investment for lining was $37.73 per ha, performance improvements after an earlier desilting were not sustained and tail end water conditions deteriorated following lining. Data also reveal that operational rigor maintaining adequate discharge, implementing rotations and taking actions against water thieves is essential if the benefits following physical intervention are to be maintained.